Children's Rights, State Criminality and Settler Colonialism: Violence and Child Arrest in Occupied East Jerusalem. (1st April 2016) - Bella Kovner; Nadera Shalhoub-Kevorkian
Abstract : Over the past few years, Palestinian children in Occupied East Jerusalem (OEJ) have faced high rates of arrest. The article examines violence against children during arrest by juxtaposing state official documents recording debates and analyses of children's rights with published reports by human rights and civil society organizations. The article suggests that arrested children in OEJ suffer from three intersecting discriminatory regimes: structural discrimination that targets them as criminals based on their ethnicity; a lack of assistance as they fall under the responsibility of neither the Palestinian nor the Israeli socio-legal systems; and limited access to welfare, justice, and educational opportunities. The article concludes by suggesting that Palestinian children face severe structural violence that amounts to state-hate criminality.